Efektivitas Bimbingan Karir Menggunakan Teknik Modeling Simbolik untuk Meningkatkan Aspek Keterlibatan Kemampuan Perencanaan Karir Peserta Didik - Zaroh, Septiani (Guidance and Counseling Study Program, Pattimura University, 2018)
Career planning is the stage that matures the career maturity and career awareness possessed by each individual. Career planning is a form of ability that must be improved in the individual to facilitate every stage of the career to be traversed. Career planning includes three indicators consisting of attitudes, abilities and involvement. This study focuses on aspects of engagement that build career planning skills. The main purpose of this research is to test the effectiveness of symbolic modeling technique in improving the involvement aspect of career planning ability of the learner. The research method used is pre-experimental design. The subjects of the study were students of Class VIII SMP Negeri 1 Kalitidu Bojonegoro academic year 2016/2017. Data were collected through an instrument of engagement aspect in career planning. Technique of data analysis use t test to compare value of pre test and post test. The results showed: (1) the largest frequency of career planning level of learners are in the less able categories; and (2) the technique of symbolic modeling effectively improves the career planning of learners.